Predominant Sea Ice Fracture Zones Around Antarctica and Their Relation to Bathymetric Features - Reiser, F.; Willmes, S.; Hausmann, U.; Heinemann, G. (Geophysical research letters, 2019)
Sea ice is of substantial importance for the Southern Ocean, as it insulates the relatively warm ocean from the cold atmosphere. Due to mechanical stress induced by wind and ocean currents, sea ice leads occur, which are characterized by open water and thin ice causing an increase of energy and moisture fluxes between ocean and atmosphere. Furthermore, they contribute to the ice production and provide a habitat for animals. Thus, it is important to gain information about the temporal and spatial distribution of leads on a circum‐Antarctic scale. So far, no operational data set exists, which provides such information. We use thermal satellite imagery from the Moderate Resolution Imaging Spectroradiometer to derive the predominant lead patterns for 2003–2018, April–September. This study provides first results for the long‐term average lead frequencies in the Southern Ocean and discusses possible links to ocean currents, tides, and the bathymetry. Plain Language Summary The polar regions are strongly influenced by sea ice, which covers large areas of the ocean's surface. Interacting with the atmosphere and the ocean, sea ice is a very dynamic surface with a large temporal and spatial variability. Under the forcing of winds and ocean currents, sea ice is subject to deformation processes causing cracks (leads) in the ice. The observation of these leads is the aim of this study since they are an important feature. For instance, open water can be found in these cracks, which enables the warm ocean (−1.7 ° C) to lose energy to the cold atmosphere. Also, sea ice forms a habitat for animals. In this study, the focus is on the Southern Hemisphere where sea ice surrounds the Antarctic continent. For the winter months, we use thermal infrared satellite images where leads appear as warm, almost linear features compared to the cold ice cover. By using computer algorithms, the cracks are detected automatically. This is the first study that shows these features in the Southern Ocean. Leads not only exist close to the coastline but also tend to appear offshore with characteristic spatial patterns. Therefore, possible links to ocean currents, tides, and bathymetry are discussed. Key Points We present the first long‐term observed daily Antarctic sea ice leads based on MODIS TIR imagery from 2003‐2018 Sea‐ice leads occur along the shelf break and are associated with the Southern Ocean Bathymetry Sea ice leads are predominantly found in regions of enhanced tidal divergence